Analysis of Business Strategy Utilizing an Integrated Swot and Balanced Scorecard Approach - Putri, Arviza Ika Permata; Ribhan; Ambarwati, Dwi Asri Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the research was to identify internal factors and external factors that affect the business of PT ASSA Rent Lampung based on the four perspectives of the balanced scorecard. This research uses mixed methods, namely qualitative methods for data collection and quantitative methods for processing data. Data collection was carried out from September 2023 to December 2023 by interview and observation. There are 3 respondents in this study, namely the branch manager, the head of the marketing department, and the head of the finance department. The results of this study indicate that the financial perspective is the most influential component of the company's internal and external factors judging from the score obtained and shows that the company's position is in cell II which is a grow and build condition indicating that the company needs an intensive and integrative strategy in the form of market penetration.